196k views
5 votes
What is the value of the expression below?

(9 divided by 3)+4( 6-7)

a)-7
b)-1
c)7
d)20

2 Answers

4 votes
First brackets:
(9 : 3) = 3(6 - 7) = (-1)
Next product
4(6 - 7) = 4(-1) = -4
Next sum
(9 : 3) + 4(6 - 7) = 3 + (-4) = -1
Answer: b) -1

User Tim Kindberg
by
5.1k points
6 votes

Answer:

b)
-1.

Explanation:

We are asked to find the value of the expression
((9)/(3))+4(6-7).

We will use order of operations (PEMDAS) to solve our given problem.

P: Parenthesis,

E : Exponent,

M/D : Multiply/Divide (From left to right)

A/S : Add/Subtract (From left to right)

First of all, we will remove parenthesis as:


3+4(-1)


3-4


-1

Therefore, the value of our given expression is
-1.

User Vashishth
by
5.4k points